COVID-19 Outcomes in Myasthenia Gravis Patients: Analysis From Electronic Health Records in the United States - Kim, Youngran; Li, Xiaojin; Huang, Yan; Kim, Minseon; Shaibani, Aziz; Sheikh, Kazim; Zhang, Guo-Qiang; Nguyen, Thy Phuong (Frontiers in Neurology, 2022)
Background: Myasthenia gravis (MG) is an autoimmune, neuromuscular condition and patients with MG are vulnerable due to immunosuppressant use and disease manifestations of dyspnea and dysphagia during the COVID-19 pandemic. Methods: We conducted a retrospective cohort study using the Optum® de-identified COVID-19 Electronic Health Record dataset. Primary outcomes including hospitalization, ventilator use, ICU admission, and death in COVID-19 with MG patients were compared to COVID-19 patients without MG: subgroups of non-MG, rheumatoid arthritis (RA), systemic lupus (SLE), and multiple sclerosis (MS). We further analyzed factors affecting mortality including age, race/ethnicity, comorbidities, and MG treatments. Results: Among 421,086 individuals with COVID-19, there were 377 MG, 7,362 RA, 1,323 SLE, 1,518 MS, and 410,505 non-MG patients. MG patients were older and had more comorbidities compared to non-MG patients and had high rates of hospitalization (38.5%), ICU admission (12.7%), ventilator use (3.7%), and mortality (10.6%) compared to all other groups. After adjusting for risk factors, MG patients had increased risks for hospitalization and ICU compared to non-MG and RA patients but similar to SLE and MS patients. The adjusted risk for ventilator use was similar across all groups but the risk for mortality in MG patients was lower compared to SLE and MS groups. Among MG patients, age 75+ and dysphagia were predictors for increased COVID-19 mortality, but MG treatments were not. Conclusions: COVID-19 patients with MG are more likely to be admitted to the hospital and require ICU care. Older age and patients with dysphagia had an increased risk of mortality.